PERBAIKAN STATUS ANTIOKSIDAN PENDERITA DIABETES TIPE 2 DENGAN TAHU KEDELAI HITAM KAYA SERAT - Nanda Triandita; Fransiska R. Zakaria; Endang Prangdimurti; Nela Eska Putri (Jurnal Teknologi dan Industri Pangan, 2016)
Type 2 diabetes mellitus (T2DM) is a non-insulin dependent diabetes, because insulin is not secreted by beta cell pancreas or dysfunction of insulin reseptors. The purposes of this research were to evaluate the effect of dietary fiber rich- tofu from black soybean on the antioxidant plasma status, malonaldehide (MDA) and hepatic marker in T2DM patients. One group (n=11) of patients was given 80 g of tofu for 30 days while the control group (n=11) was not. No significant differences was observed pertaining the characteristics of both groups before interventions (age, body mass index, body weight, body high, systolic blood pressure, diastolic blood pressure and fasting blood glucose). The antioxidant activity, MDA and AST/ALT of both groups were analyzed from plasma at day-0 and day-30. Antioxidant activity was analyzed by DPPH method, MDA level with TBARS method, and AST/ALT by International Federation of Clinical Chemistry (IFCC) method. The result showed that the plasma antioxidant increased (4.77±9.49%), but the MDA (2.11±1.73 nmol/mL) and AST (7.73±16.72 U/L)/ ALT (3.55±12.79 U/L) level decreased. Rich dietary fiber tofu from black soybean may have potential use for improving the health status of T2DM patients.